Ответы и объяснения

2014-03-20T00:01:52+00:00
A1. a) 7^(-2)*7^(4)=7^(-2+4)=7^2=49
       b) 2^18 / 2^21= 2^(18-21)=2^(-3)= 1/8
       c)9^(-3) * 3^(8) / 27^(2) =  3^(-6+8) / 3^(3*2) = 3^2 / 3^6 = 3^(2-6)= 3^(-4)=1/81
A.2
      a) = 9a^(2)b^(-2)            b) = 6x^(-6+7)y^( -5+4)= 6*x*y^(-1)

A3. 
      536*10^11

A4.
ИТОГОВЫЙ ОТВЕТ СМОТРЕТЬ ТУТ -    (6,75/8,1) * 10^4 = 2,5 * 10^4 !!!!!!!!

675         10            225       25
------   *   ------   =      ----   =  ----  = 2,5
100         81             90        10

 
B1 a^(-17+8)                     a^(-9)
           /               ====        /         =====  a^(-9+12)     => a^3
        a^(-4*3)                     a^(-12)

.